Eisbär mit Seehund ... - www.noe-3d.at (Zenodo, 2022)
Sculpture of a polar bear holding a seal with its right paw. The figures from 1902 were created by Otto Jarl and are located in front of the Jörgerbad in Vienna's 17th district. Source: Objaverse 1.0 / Sketchfab ...